Classical Solution and Edge Effect in the Problem of Stability of an Axially Compressed Cylindrical Shell - Guyk A. Manuylov; Sergey B. Kosytsyn; Maksim M. Begichev (Communications - Scientific letters of the University of Zilina, 2020)
The classical solution for critical stresses in the problem of stability of a circular longitudinally compressed cylindrical shell consists of two terms, reflecting the ability of the shell to resist buckling due to bending and membrane deformations. However, with usual boundary conditions the classical solution appears only with the absence of the Poisson expansion of a shell. With a non-zero Poisson’s ratio, an axisymmetric edge effect presents. It reduces the critical load and causes the initial arrangement of its own forms to change as the load increases.